THE INFLUENCE OF SERIES PICTURE MEDIA ON WRITING STUDENTS IN CLASS V STUDENTS OF SDN LIMBANGAN WETAN 02 LEARNING LANGUAGE (International Conference on Elementary Education, 2018)
Errors in learning that are too rigid give the impression that writing is difficult. Not many teachers have been able to present the subject matter in the right and interesting way. This research aims to find out the Effect of Series Picture Media on Student Writing Skills. The research method uses descriptive quantitative with a population of 31 consisting of 31 control class students and 31 experimental classes. The research instrument is the validity of the problem with the number of 15 valid questions 11 questions. The Control Class shows the Kolmogorov-Smirnov coefficient 0.239> 0.05 in the 2-tailed Sig 0,000 indicating a significant data distribution of normal patterns. Then in the Experiment Class Kolmogorov-Smirnov coefficient 0.213> 0.05 on a 2-tailed Sig 0.089> 0.05 and the data can be said to be normally distributed, the data is homogeneous on the Levene Statistic coefficient of 3.339 in Asym Sig 0.070> 0.05 in hypothesis testing with t test after the results of the writing skills of the control class and experiment are submitted to the testing of the hypothesis produced t count 4.045> t table 2.00 at the significant level of 5% or 0.05 so that Ho is rejected, it is said that the use of the series image media has a significant effect on student writing skills.